Thyroiditis after mRNA Vaccination for COVID-19 - Arunava Saha; Sanjita Chittimoju; Nitin Trivedi (Case Reports in Endocrinology)
Background. SARS-CoV-2 has been known to cause multisystemic involvement, gaining entry through ACE-2 and TMPRSS2 receptors. COVID-19 vaccine-associated thyroiditis cases are now being reported. Case Report. Case 1. A 36-year-old woman with a history of right hemithyroidectomy for a benign thyroid nodule, on a stable dose of levothyroxine with euthyroid labs, presented with progressively worsening left neck pain, episodic palpitations, and heat intolerance after the second dose of mRNA1273 (Moderna) vaccine. Examination revealed an enlarged and tender left lobe of the thyroid with suppressed TSH but normal free T4 and ESR, signifying subacute thyroiditis. She was managed conservatively without corticosteroids or beta-blockers, and her symptoms resolved. A follow-up revealed increasing TSH, and levothyroxine was restarted. Case 2. A 33-year-old man with a history of anxiety disorder on Sertraline, presented with a two-week history of palpitations, heat intolerance, and 10-pound weight loss after the second dose of BNT162b2 (Pfizer-BioNTech) vaccine. Examination revealed a normal thyroid gland with no tenderness with elevated thyroid peroxidase and thyroglobulin antibodies. Ultrasound showed a diffusely heterogeneous thyroid with increased vascularity, suggesting silent thyroiditis. Follow-up revealed a hypothyroid phase with high TSH for which levothyroxine supplementation was started. Discussion. COVID-19 vaccine-associated subacute and silent thyroiditis have occurred following all three kinds of available vaccines, characterized by an initial thyrotoxic phase, followed by a hypothyroid phase and a recovery phase. Hypotheses include an immune response triggering thyroid inflammation or cross-reactivity with viral proteins. Conclusions. COVID-19 vaccine-associated thyroiditis is rare, but long-term monitoring of these patients is essential to ensure appropriate diagnosis and management of the potential hypothyroid phase.